2010
DOI: 10.1177/1941738109338359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Scapulothoracic Bursitis and the Snapping Scapula

Abstract: Context:Symptomatic scapulothoracic bursitis and crepitus are disorders of the scapulothoracic articulation that are often poorly understood. They can be a source of persistent pain and dysfunction in the active overhead throwing athlete. It is important to distinguish between scapulothoracic bursitis and scapulothoracic crepitus. Scapulothoracic bursitis refers to inflammation of the bursae secondary to trauma or overuse owing to sports activities or work. Scapulothoracic crepitus is defined by a grinding, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 44 publications
0
56
0
5
Order By: Relevance
“…Most patients respond to nonoperative treatment, including activity modification, nonsteroidal anti-inflammatory drugs, physical therapy, and injections of steroids and/ or local anesthetics. 4 For patients who do not respond to conservative measures, surgery is an effective option. 5 The arthroscopic anatomy of the space between the scapula and thoracic wall has been described, and the results of arthroscopic treatment of SSS have been published.…”
mentioning
confidence: 99%
“…Most patients respond to nonoperative treatment, including activity modification, nonsteroidal anti-inflammatory drugs, physical therapy, and injections of steroids and/ or local anesthetics. 4 For patients who do not respond to conservative measures, surgery is an effective option. 5 The arthroscopic anatomy of the space between the scapula and thoracic wall has been described, and the results of arthroscopic treatment of SSS have been published.…”
mentioning
confidence: 99%
“…One review of 89 cases of scapulothoracic bursitis found that an anatomic abnormality was responsible for symptoms in 43% of the cases [30]. The Luschka Tubercle and excessive anterior angulation of the superior angle of the scapula are examples of skeletal abnormalities.…”
Section: Abnormal Scapulothoracic Articulationmentioning
confidence: 99%
“…Skapular bursitler sıklıkla hareket ile artan ağrı şikayeti ile başvururlar ve skapulanın hareketi ile sesli ve palpabl krepitasyon olabilir 1 Bursitler genellikle altta yatan inflamatuar veya travmatik nedenlere bağlı olarak görülmektedir. Olgumuzda skapulada kitleye eşlik eden büyük boyutlu bursit olması ayırıcı tanıda malignite de düşünmemize neden oldu.…”
Section: Introductionunclassified